Kraven the hunter [videorecording (Blu-Ray)] - Wenk, Richard; Marcum, Art; Holloway, Matt; Taylor-Johnson, Aaron, 1990-; DeBose, Ariana, 1991-; Hechinger, Fred; Nivola, Alessandro; Abbott, Christopher, 1986-; Crowe, Russell, 1964-; Miller, Levi, 2002-; Wallfisch, Benjamin; Galpérine, Evgueni; et al. (Sony Pictures Home Entertainment, 2025)
Kraven is a man whose complex relationship with his ruthless gangster father, Nikolai Kravinoff, starts him down a path of vengeance with brutal consequences, motivating him to become not only the greatest hunter in the world, but also one of its most feared.